2023
DOI: 10.3390/molecules28166073
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Polysaccharides: A Review of Synthetic Approaches, Biological Activity and the Structure–Activity Relationship

Abstract: Natural polysaccharides are macromolecular substances with great potential owing to their wide biological activity and low toxicity. However, not all polysaccharides have significant pharmacodynamic activity; hence, appropriate chemical modification methods can be selected according to the unique structural characteristics of polysaccharides to assist in enhancing and promoting the presentation of their biological activities. This review summarizes research progress on modified polysaccharides, including commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Polysaccharides, due to their versatility with numerous reactive functional groups such as hydroxyl, amino, and carboxyl, are highly adaptable to chemical reactions that introduce new groups into their structure . Any modification or additive introduced in the manufacturing process carries the potential to impact the degradability of materials, alter the nature of decomposition products, and ultimately shape the environmental destiny of the product.…”
Section: Bioplasticsmentioning
confidence: 99%
“…Polysaccharides, due to their versatility with numerous reactive functional groups such as hydroxyl, amino, and carboxyl, are highly adaptable to chemical reactions that introduce new groups into their structure . Any modification or additive introduced in the manufacturing process carries the potential to impact the degradability of materials, alter the nature of decomposition products, and ultimately shape the environmental destiny of the product.…”
Section: Bioplasticsmentioning
confidence: 99%
“…In recent studies, it has been observed to enhance the proliferation of embryonic stem cells and demonstrate anticoagulant properties [ 28 , 29 ]. Numerous studies indicate that the inherent bioactivities of native polysaccharides are relatively low but can be significantly improved through molecular modifications [ 30 ]. Sulfation or carboxymethylation emerges as a viable approach to address the limited water solubility and amplify the biological activity of natural polysaccharides through the alteration of their structural and conformational characteristics [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, natural compounds can undergo chemical modifications to bolster their potency, selectivity, and pharmacokinetic properties [18,19]. Medicinal chemists employ techniques like structure-activity relationship (SAR) studies and combinatorial chemistry to design and synthesize analogs with enhanced anticancer activity [20,21].…”
Section: Introductionmentioning
confidence: 99%